Pengujian Fitokimia dan Penentuan Kadar Flavonoid Ekstrak Etanol Bunga Telang (Clitoria ternatea L.) - Lusi Puspitasari, Ni Wayan; Sukma Sanjiwani, Ni Made; Wahyu Udayani , Ni Nyoman (Usadha, 2024)
Flavonoids are polyphenolic compounds, so they have the chemical properties of phenolic compounds, which are slightly acidic, soluble in bases, and are polyhydroxy (hydroxy groups) and polar. Flavonoids are found in many plants such as butterfly pea. This study aims to determine the presence or absence of flavonoids in the ethanol extract of butterfly peas and the levels of flavonoids contained in the extract of butterfly peas (Clitoria ternatea L.). This research was conducted by extracting the butterfly pea flower by maceration with ethanol and phytochemical testing of flavonoids. Flavonoid content was determined by the Chang method using UV-visible spectrophotometry. The data obtained were analyzed using Lambert Beer's law. The results of this study indicate that the ethanol extract of butterfly pea flowers positively contains flavonoid compounds which cause a red color after phytochemical testing. Determination of the levels carried out obtained an average level of flavonoids of 0.28107%.